2014
DOI: 10.1039/c4ra09073j
|View full text |Cite
|
Sign up to set email alerts
|

Easy preparation of an MRI contrast agent with high longitudinal relaxivity based on gadolinium ions-loaded graphene oxide

Abstract: As far as the longitudinal relaxivity (r 1 ) is concerned, gadolinium ions (Gd 3+ )-based MRI contrast agents modified by traditional carriers do not appear to be far superior to the clinically used Magnevist. In this study, a type of MRI contrast agent (Gd 3+ @CGO) possessing a significantly high r 1 value was easily prepared using a carboxyl-functionalized graphene oxide (CGO) as a nanocarrier to directly interact with GdCl 3 $6H 2 O. With 2.8 wt% of Gd 3+ loaded on CGO, the prepared Gd 3+ @CGO shows good di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…For instance, Ren et al reported a carboxyl-functionalized GO loaded with 2.8 wt% Gd 3+ . The NPs afforded good colloidal stability and a high r 1 of 63.8 mM -1 s -1 (Gd) at 3.0 T 166 . Similarly, Mn 2+ can be loaded onto graphene or GO.…”
Section: Nanoparticle or Macromolecule Contrast Agents With Enhanced mentioning
confidence: 99%
“…For instance, Ren et al reported a carboxyl-functionalized GO loaded with 2.8 wt% Gd 3+ . The NPs afforded good colloidal stability and a high r 1 of 63.8 mM -1 s -1 (Gd) at 3.0 T 166 . Similarly, Mn 2+ can be loaded onto graphene or GO.…”
Section: Nanoparticle or Macromolecule Contrast Agents With Enhanced mentioning
confidence: 99%
“…In the XPS spectrum, Gd-usNGO-PEG showed that the binding energy value of the gadolinium peak (Gd 4d) was 142.8 eV, which confirmed the successful Gd 3+ chelation (Figure b). Furthermore, the binding energy values of both N 1s and O 1s in Gd-usNGO-PEG shifted to 400.0 and 532.9 eV, compared with 401.2 and 533.3 eV in usNGO-PEG, respectively (Figure c,d) . The XPS spectra of C 1s in usNGO-PEG included peak 1 (CC/C–C, 285.6 eV), peak 2 (C–O/C–O–C, ∼286.8 eV), and peak 3 consisting of CO (carbonyl, ∼288.3 eV) and O–CO (carboxyl, ∼290.2 eV).…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, the binding energy values of both N 1s and O 1s in Gd-usNGO-PEG shifted to 400.0 and 532.9 eV, compared with 401.2 and 533.3 eV in usNGO-PEG, respectively (Figure 3c,d). 35 The XPS spectra of C 1s in usNGO-PEG included 33,36 From these changes in the XPS spectra, we speculated that the coordination interaction occurred between Gd 3+ and the electron donors N, O, and C O. In addition, the amine density of Gd-usNGO-PEG (detected by the O-phthalaldehyde (OPA) method 37 ) decreased to 2.2 × 10 −4 mmol per 1 mg usNGO-PEG.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 98%
“…These include its low cost and improved water dispersibility owing to the abundance of hydrophilic oxygen-containing groups in its structure. 14 Materials like SPIONs (superparamagnetic iron oxide nanoparticles) are themselves good T 2 contrast agents, but coupling them with reduced graphene oxide prevents their clumping thus improving their circulation time and efficiency. 15 As stated earlier about the toxic nature of Gd 3+ ions, on coupling Gd 2 O 3 with GO, the release of Gd 3+ ions can be eliminated while enhancing the solubility in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%